Helping hospital professionals to implement Advance Care Planning in daily practice: a European Delphi study from field experts. (September 2019) - Vanderhaeghen, Birgit; Bossuyt, Inge; Menten, Johan; Rober, Peter
Background: Advance Care Planning (ACP) communication is difficult to implement in hospital. Possibly this has to do with the fact that the concept is not well tuned to the needs of hospital professionals or that they experience implementation barriers in practice. Aims: The aim of this study was to investigate what is valued in having ACP conversations by hospital professionals (physicians, nurses, psychologists and social workers) and what they experience as barriers and facilitating factors for having ACP conversations with patients. Methods: A Delphi study consisting of two rounds with respectively 21 and 19 multidisciplinary experts from seven European countries was organised. Data were analysed using content analysis and descriptive statistics. Results: Participants agreed that ACP is valued mostly because it is seen to improve transmural continuation of care, emotional processing of the loss of a patient, and serenity at the end of life. Reported barriers are patient characteristics blocking patient-centred communication and a lack of knowledge to have these conversations. An important facilitator is multidisciplinary cooperation. Conclusions: There is consensus by experts from different settings and countries suggesting that these results can theoretically be applied to hospital settings in Europe. This study reveals that hospital professionals value ACP in hospital practice, but that they encounter several barriers to its implementation.